Stability and reaction dynamics of trifluorinated indolylfulgides - Brust, Thomas (2009)
Quantum efficiencies and ultrafast dynamics of the ring-closure and ring-opening reaction of a trifluorinated dicyclopropyl indolylfulgide with improved photostability are investigated by stationary and ultrafast absorption spectroscopy. The ring-closure reaction occurs on the time scale of 200 fs and is found to be temperature independent (T = 287 – 333 K). However, an activated behaviour is observed for the ring-opening reaction. A comparison with the corresponding non-substituted indolylfulgide shows that the dicyclopropyl group favours the open isomer via lower cyclisation and higher cycloreversion quantum efficiencies and faster dynamics of the ring-opening reaction.